8с + 4 (1-с) 2(степень) = 4ab + 2 (a-b) 2(степень) = 3(х+у) 2(степень) — 6ху =

8с + 4 (1-с) 2(степень) =
4ab + 2 (a-b) 2(степень) =
3(х+у) 2(степень) — 6ху =

  • 1. 8с + 4 (1-с)^2 =8c + 4(1+c^2-2c)=8c+4+4c^2-8c=4+4c^2=4(1+c^2)

    2. 4ab + 2 (a-b)^2 =4ab + 2(a^2 + b^2 -2ab)=4ab + 2a^2 + 2b^2 — 4ab=2(a^2+b^2)

    3. 3(х+у)^2 — 6ху =3(x^2 + y^2 + 2xy) — 6xy = 3x^2 + 3y^2 + 6xy -6xy = 3(x^2 + y^2)

  • 8с+4(с^2-2c+1)=8c+4c^2-8c+4=4c^2+4=

    4c^2=-4

    c^2=-1

    нет ответа

    2)4ab+2(a-b)^2=4ab+2a^2-4ab+2b^2=2(a-b)(a+b)

    3(х+у)^2 — 6ху =3(x^2 + y^2 + 2xy) — 6xy = 3x^2 + 3y^2 + 6xy -6xy = 3(x^2 + y^2)